2018
DOI: 10.1073/pnas.1806760115
|View full text |Cite
|
Sign up to set email alerts
|

Systems genetic analysis of inversion polymorphisms in the malaria mosquito Anopheles gambiae

Abstract: Inversion polymorphisms in the African malaria vector segregate along climatic gradients of aridity. Despite indirect evidence of their adaptive significance, little is known of the phenotypic targets of selection or the underlying genetic mechanisms. Here we adopt a systems genetics approach to explore the interaction of two inversions on opposite arms of chromosome 2 with gender, climatic conditions, and one another. We measure organismal traits and transcriptional profiles in 8-d-old adults of both sexes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 91 publications
0
64
0
Order By: Relevance
“…Of these 44 genes, 35 showed significant differences in expression between arrangements of In(2La). This fraction of differentially expressed genes with significant SNPs, 79.5% (35/44), is much higher than the overall fraction of differentially expressed genes within In(2La) between arrangements (~60%; Cheng et al 2018). Two of our top-ranking candidate genes have presumed roles in response to environmental stimulus.…”
Section: Association Mapping Within the 2la Inversionmentioning
confidence: 79%
See 2 more Smart Citations
“…Of these 44 genes, 35 showed significant differences in expression between arrangements of In(2La). This fraction of differentially expressed genes with significant SNPs, 79.5% (35/44), is much higher than the overall fraction of differentially expressed genes within In(2La) between arrangements (~60%; Cheng et al 2018). Two of our top-ranking candidate genes have presumed roles in response to environmental stimulus.…”
Section: Association Mapping Within the 2la Inversionmentioning
confidence: 79%
“…Most significant SNPs were found in non-coding regions: we found only four synonymous variants among our set of significant sites, and no nonsynonymous variants. Previous studies have found many differences in transcription between inversion arrangements at In(2La) (Cassone et al 2011;Cheng et al 2018), allowing us to ask whether the same genes containing significant SNPs also showed evidence for differential expression. We crossreferenced expression profiles from Cheng et al (2018) with our list of 57 candidate genes and found data for 44 of them.…”
Section: Association Mapping Within the 2la Inversionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently implicated in nutritional homeostasis in Drosophila [54] and is known to interact with the TOR pathway [55], which has been identified as a target of ecological adaptation in Drosophila [56, 57] and An. gambiae [58]. The sweep appears largely confined to island individuals in the LVB, but the cluster of haplotypes also includes those from Gabon, Burkina Faso, and Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila species has found chromosomal inversion structure to have little effect on gene expression patterns (Huang et al 2015;Fuller et al 2016;Lavington and Kern 2017;Said et al 2018;Cheng et al 2018) . Our observation that somatic pairing is disrupted only partially and only in the relatively small regions immediately surrounding inversion breakpoints is consistent with these observations and suggests that dipteran chromatin structures are particularly resilient to changes imposed by genome structure polymorphism.…”
Section: Recent Work In a Gambiae Andmentioning
confidence: 99%